UNCHEHARA’S PHOOL METAL CRAFT: HERITAGE, DECLINE, AND THE URGENT NEED FOR PRESERVATION - Kanungo, Manjari; Biswas, Kakoli (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The Unchehara Phool metal craft of Satna district Madhya Pradesh represents a traditional bronze-working art which originates from the metallurgical practices of the Tamrakar community. The craft which started in the Unchehara area used Phool a special copper-tin alloy to create bells and ritual objects and utensils for domestic use. The items which originated during the Gupta period functioned as essential domestic items and sacred objects and elements of communal identity. The research studies the historical development and current state of the craft by documenting its operational methods and equipment and its cultural significance. The craft maintains its existence through approximately fifteen practitioners who produce work for local fairs and temple events but its heritage remains extensive. The study uses oral histories and fieldwork and archival sources to analyze the social and economic and cultural elements that contributed to its decline. The study presents a historical and modern narrative which enhances the documentation of India's metallurgical heritage while it shows the need for protection initiatives to preserve endangered traditional knowledge.